The African Union's Africa: New Pan-African Initiatives in Global Governance. - Edozie, Rita Kiki (Ruth Simms Hamilton African diaspora series., 2014)
The African Union's Africa: New Pan-African Initiatives in Global Governance examines the initiatives of the Pan-African global governance institution the African Union (AU) as the organization and its precursor commemorate their Jubilee as international actors. Taking a unique approach, the book seeks to explain the AU through a theoretical framework referred to as "the African Union phenomenon," capturing the international organization's efforts to transform the national politics of Africa as well as to globalize the practice of African politics. The authors examine Africa's self-determined international norms and values such as Pan-Africanism, African Solutions to African Problems, Hybrid Democracy, Pax Africana, and the African Economic Community to demonstrate that Africa-the world's least developed region-is composed of crucial values, institutions, agents, actors, and forces that are, through the AU, contributing to the advancement of contemporary global development. The book reveals how in the areas of cultural identity, democracy, security, and economic development Africans are infusing new politics, economics, and cultures into globalization representing the collective will and imprint of African agency, decisions, ideas, identities, practices, and contexts. Via a Pan-African vision, the AU is having both regional and global impact, generating exciting possibilities and complicated challenges